The effects of Berberis vulgaris consumption on plasma levels of IGF-1, IGFBPs, PPAR-γ and the expression of angiogenic genes in women with benign breast disease: a randomized controlled clinical trial - Saeed Pirouzpanah; Sanaz Asemani; Ali Shayanfar; Behzad Baradaran; Vahid Montazeri (BMC, 2019)
Abstract Background The present study was designed to investigate the effects of Berberis vulgaris (BV) juice consumption on plasma levels of insulin-like growth factor (IGF-1), IGF-binding proteins (IGFBPs), and the expression of PPAR-γ, VEGF and HIF in women with benign breast disease. Methods This parallel design randomized, double-blind controlled clinical trial was conducted on 85 eligible patients diagnosed with benign breast disease. They were assigned randomly into either BV juice group (n = 44, BV juice: 480 ml/day) or placebo group (n = 41, BV placebo juice: 480 ml/day) for 8 weeks intervention. Participants, caregivers and those who assessed laboratory analyses were blinded to the assignments. Plasma levels of biomarkers were measured at baseline and after 8 weeks by ELISA. Quantitative real-time PCR was used to measure the fold change in the expression of each interested gene. Results The compliance of participants was 95.2% and 40 available subjects analyzed in each group at last. Relative treatment (RT) effects for BV juice caused 16% fall in IGF-1 concentration and 37% reduction in the ratio of IGF-1/1GFBP1. Absolute treatment effect expressed 111 ng/ml increased mean differences of IGFBP-3 between BV group and placebo. Plasma level of PPAR-γ increased in both groups but it was not significant. Fold changes in the expressions of PPAR-γ, VEGF and HIF showed down-regulation in the intervention group compared to placebos (P < 0.05). Conclusions The BV juice intervention over 8 weeks was accompanied by acceptable efficacy and decreased plasma IGF-1, and IGF-1/IGFBP-1 ratio partly could be assigned to enhanced IGFBP-1 level in women with BBD. The intervention caused reductions in the expression levels of PPAR, VEGF, and HIF which are remarkable genomic changes to potentially prevent breast tumorigenesis. Trial registration IRCT2012110511335N2. Registered 10 July 2013 (retrospectively registered).